2013
DOI: 10.1371/journal.pone.0069534
|View full text |Cite
|
Sign up to set email alerts
|

Copper Oxide Nanoparticles Induced Mitochondria Mediated Apoptosis in Human Hepatocarcinoma Cells

Abstract: Copper oxide nanoparticles (CuO NPs) are heavily utilized in semiconductor devices, gas sensor, batteries, solar energy converter, microelectronics and heat transfer fluids. It has been reported that liver is one of the target organs for nanoparticles after they gain entry into the body through any of the possible routes. Recent studies have shown cytotoxic response of CuO NPs in liver cells. However, the underlying mechanism of apoptosis in liver cells due to CuO NPs exposure is largely lacking. We explored t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
205
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 319 publications
(219 citation statements)
references
References 57 publications
13
205
0
1
Order By: Relevance
“…65 Cellular alterations caused by TiO 2 NPs, such as changes in the redox state, insufficient defense of antioxidant enzymes, and mitochondrial depolarization, may lead to cell apoptosis by activating apoptotic-signaling pathways. 66 Siddiqui et al 41 observed a decrease in the mitochondrial membrane potential followed by an increase in the Bax/Bcl-2 ratio, suggesting a mediator role of the mitochondria in ZnO NP-induced apoptosis. Shimizu et al 45 found that prenatal exposure to anatase TiO 2 NPs altered the expression of genes related to brain …”
Section: Interaction Of Nps With Mitochondriamentioning
confidence: 99%
See 1 more Smart Citation
“…65 Cellular alterations caused by TiO 2 NPs, such as changes in the redox state, insufficient defense of antioxidant enzymes, and mitochondrial depolarization, may lead to cell apoptosis by activating apoptotic-signaling pathways. 66 Siddiqui et al 41 observed a decrease in the mitochondrial membrane potential followed by an increase in the Bax/Bcl-2 ratio, suggesting a mediator role of the mitochondria in ZnO NP-induced apoptosis. Shimizu et al 45 found that prenatal exposure to anatase TiO 2 NPs altered the expression of genes related to brain …”
Section: Interaction Of Nps With Mitochondriamentioning
confidence: 99%
“…34 The impact of NPs on offspring is another concern because the CNS exhibits considerable plasticity in the early stage of life and could be significantly influenced by environmental invasions encountered during the fetal period. 41 Unfortunately, studies have revealed that NPs entering the maternal body during gestation may harm fetal development through direct or indirect mechanisms. Even small amounts of particles in the maternal blood can translocate to the fetal compartment.…”
Section: Relationship Between Nms and Cns Dysfunctionmentioning
confidence: 99%
“…The inhibition of Erk activation promoted viability loss in cells treated with both low and high concentrations of CuONP, which implies a prosurvival function for Erk in this context. Several studies reported that CuONP induced reactive oxygen species (ROS) generation in different cells, 10,13,18,32 including keratinocytes 16 and fibroblasts. 33 For example, Alarifi et al reported that CuONP induced dosedependent cell death and ROS generation in keratinocytes.…”
mentioning
confidence: 99%
“…Siddiqui et al [81] reported that CuO nanoparticles (average size 22 nm) induced cytotoxicity in human hepatocellular carcinoma (HepG2) cells in a dose-dependent manner (2-50 mg/mL) and reported that tumor suppressor gene p53 and apoptotic gene caspase-3 were upregulated upon exposure to CuO nanoparticles. Figure 3A shows the field emission transmission electron microscopy (FETEM) image (inset with a higher magnification) of CuO nanoparticles.…”
Section: Copper Oxide (Cuo Cu2o) Nanoparticlesmentioning
confidence: 99%
“…Figure 3B reports the viability of HepG2 cells, as assayed by (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) (MTT), incubated for 24 h with CuO nanoparticles at different concentrations up to 50 µg/mL. Cell viability was significantly reduced in a concentration-dependent manner (83%, 69%, 52%, 34% and 28%) when the cells were exposed to varying concentrations of CuO nanoparticles (2, 5, 10, 25 and 50 mg/mL) [81]. Sun et al [82] exposed the A549, H1650 and CNE-2Z cell lines to chemically synthesized CuO nanoparticles and reported high toxicity on cell viability.…”
Section: Copper Oxide (Cuo Cu2o) Nanoparticlesmentioning
confidence: 99%